2015
DOI: 10.1111/febs.13292
|View full text |Cite
|
Sign up to set email alerts
|

A product of RpfB and RipA joint enzymatic action promotes the resuscitation of dormant mycobacteria

Abstract: Resuscitation-promoting factor proteins (Rpfs) are known to participate in reactivating the dormant forms of actinobacteria. Structural analysis of the Rpf catalytic domain demonstrates its similarity to lysozyme and to lytic transglycosylases -the groups of enzymes that cleave the b-1,4-glycosidic bond between N-acetylmuramic acid (MurNAc) and GlcNAc, and concomitantly form a 1,6-anhydro ring at the MurNAc residue. Analysis of the products formed from mycobacterial peptidoglycan hydrolysis reactions containin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
49
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 58 publications
(56 citation statements)
references
References 54 publications
2
49
0
2
Order By: Relevance
“…Consistent with these findings, we previously showed that RpfB acts through a mechanism, which resembles that of lytic transglycosylases, rather than that of lysozyme . Consistently, the product of the joint action of RpfB and RipA, is the anhydro‐muropeptide N ‐acetylglucosaminyl‐(ß1→4)‐ N ‐acetyl‐1,6‐anhydromuramoyl‐ l ‐alanyl‐ d ‐isoglutamate (anhydroGMDP) . Similar to other lytic transglycosylases, RpfB cleaves the β‐1, 4‐glycosidic bond between NAM and NAG with the formation of a 1,6‐anhydro ring at the NAM residue.…”
Section: Pgn Degradation and Bacterial Return To Lifesupporting
confidence: 65%
See 4 more Smart Citations
“…Consistent with these findings, we previously showed that RpfB acts through a mechanism, which resembles that of lytic transglycosylases, rather than that of lysozyme . Consistently, the product of the joint action of RpfB and RipA, is the anhydro‐muropeptide N ‐acetylglucosaminyl‐(ß1→4)‐ N ‐acetyl‐1,6‐anhydromuramoyl‐ l ‐alanyl‐ d ‐isoglutamate (anhydroGMDP) . Similar to other lytic transglycosylases, RpfB cleaves the β‐1, 4‐glycosidic bond between NAM and NAG with the formation of a 1,6‐anhydro ring at the NAM residue.…”
Section: Pgn Degradation and Bacterial Return To Lifesupporting
confidence: 65%
“…In contrast to HEWL, RpfB has no equivalent to c‐type lysozyme's Asp52, and a sole extra acidic amino acid in the substrate binding cleft, Asp312, exists only in RpfB, and is not conserved in its M. tuberculosis homologs. Consistent with these findings, we previously showed that RpfB acts through a mechanism, which resembles that of lytic transglycosylases, rather than that of lysozyme . Consistently, the product of the joint action of RpfB and RipA, is the anhydro‐muropeptide N ‐acetylglucosaminyl‐(ß1→4)‐ N ‐acetyl‐1,6‐anhydromuramoyl‐ l ‐alanyl‐ d ‐isoglutamate (anhydroGMDP) .…”
Section: Pgn Degradation and Bacterial Return To Lifesupporting
confidence: 64%
See 3 more Smart Citations